If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = -16t + vt + c Reorder the terms: 0 = c + -16t + tv Solving 0 = c + -16t + tv Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 0 + -1c = c + -16t + -1c + tv Remove the zero: -1c = c + -16t + -1c + tv Reorder the terms: -1c = c + -1c + -16t + tv Combine like terms: c + -1c = 0 -1c = 0 + -16t + tv -1c = -16t + tv Divide each side by '-1'. c = 16t + -1tv Simplifying c = 16t + -1tv
| 9z-11=65+3z | | (3x-2)(3x+2)=9x^2-18x+9-6(4-x)+12x | | x(12-104)=x(4-8) | | 2(-5x-7)+10x=-8 | | 8-7x=116-28x | | 2(q-7)+3=19 | | -4=2(x-6) | | a+9=3a-1 | | -42-7=9x+22 | | -6y-9y=-1 | | (3x-2)(3x+2)=(3x-3)(3x+3)-6(4-x)+12x | | 4(t-13)+8=20 | | (-4v^2+8v+4)+(3v^2-5v-7)-(-v^2+5v+4)=0 | | 2(q+2)=10 | | (12x-9)+(2x+21)=360 | | 2 ( q + 2 ) = 10 | | (-.517m)(-.6n)= | | 2(s-11)+7=15 | | 5+13p-3=9p+46-7p | | 12x-5x=27 | | 13-p=16 | | 12x-5x=0 | | -.6b=-3 | | 6s(-142857)= | | 3[5-3(4-c)]-5=5[3(5c-4)+2]-26 | | 2(v+3)-3=15 | | (12x+9)+(2x+21)=360 | | 5a(3.4b)= | | 7(2x-1)=8x-25 | | (2x+3)(9x+6)=43+2(3x+1)(3+1) | | -2.7(4y)= | | a=215.5t+2500 |